Exploring the Digitalization of Historic Buildings for Urban Heritage Governance in Kayutangan Heritage Malang, Indonesia - Santosa, Herry; Sutikno, Fauzul Rizal; Yudono, Adipandang; Adhitama, Muhammad Satya; Zuliana, Eni (Department of Urban and Regional Planning, Universitas Diponegoro, 2023)
Digital technology is significantly transforming the documentation, analysis, and preservation of historic buildings from the past. The recent development of digital tools and techniques can be helpful for various activities such as documentation, monitoring, and decision-making processes. An in-depth study of the advantages and disadvantages of digitalization highlights the importance of integrating digital approaches into urban cultural heritage governance practices. This paper aims to explore advances in digitalization tools, focusing on the Kayutangan heritage in Malang, Indonesia, highlighting the importance of incorporating virtual tourism through precision and accuracy in visual data mining and enriching the diversity of uses of the latest digital technology. These innovations cover many aspects, including the art of complex 3D modeling applied to historical editions, the creative fields of virtual reality and augmented reality and progressive developments in Metaverse technology. This study also points out the strengths and weaknesses of various types of digital technology development in historic buildings and areas. Eventually, this study emphasizes implementing a web-based Kayutangan digital heritage information system integrated with the Metaverse gateway and complemented by a comprehensive user assessment survey to improve the overall user experience. This study unveils a favorable public assessment regarding the Kayutangan Metaverse development and, all at once, strengthens efforts in advancing smart governance innovations for managing the historic Kayutangan area. The findings from user assessment questionnaires and analysis calculations indicate that the development of Kayutangan Metaverse technology is highly rated. Furthermore, it is essential to focus on enhancing the representation of individuals and objects, improving virtual surroundings, and increasing the accessibility of human-related information content in such environments.